Enhanced elastic behavior of all-carbon composites reinforced by in-situ synthesized morphed graphene. (November 2019) - Calderon, H.A.; Alvarez Ramirez, F.; Barber, D.; Hadjiev, V.G.; Okonkwo, A.; Ordoñez Olivares, R.; Estrada Guel, I.; Robles Hernandez, F.C.
Abstract: We present the mechanical properties of all-carbon composites reinforced with in situ incorporated morphed graphene nanostructures by means of high energy ball milling and spark plasma sintering. The composites demonstrate enhanced elasticity for carbon sp 3 /sp 2 ratio ≈1/4. High resolution TEM characterization and molecular dynamics simulations show that this bonding type ratio is due mostly to the morphed graphene structures. Specifically, the presence of Rh6, crosslinked graphene-like, nanostructures is attributed to the enhanced elastic properties of these all-carbon composites. The improvements in mechanical properties is approximately 2 orders of magnitude when compared to similar composites produced with graphene. Graphical abstract: Image 1